Studi Komparatif Pelaksanaan Hak Restitusi Bagi Korban Perdagangan Orang di Indonesia - Bui, Ursula Andriani (CT. Rajawali media Utama, 2024)
This study aims to analyze the effectiveness of the law on the fulfillment of the right of restitution Against Trafficking in Persons in Indonesia. This study uses normative legal methods. The results of this study are (1) the fulfillment of the right of restitution to victims of trafficking in Persons is regulated in Law regulated in Law Number 21 of 2007 concerning the eradication of human trafficking, the Criminal Procedure Code (KUHAP) in Compensation for Losses resulting from criminal acts, Law No. 31 of 2014 amendments to Law no. 13 of 2006 concerning the protection of witnesses and victims. (2) the effectiveness of the fulfillment of the right to restitution of victims of trafficking in Persons has not been effective because because criminal justice has not provided certainty regarding the fulfillment of restitution, and the absence of consistency in the handing down of decisions regarding the rights of restitution for TIP victims in Indonesia.